Beginning on an age‐friendly journey: Barriers to implementing age‐friendly initiatives. (16th March 2021) - Neville, Stephen; Napier, Sara; Shannon, Kay; Adams, Jeffery
Abstract: Objective: To explore the barriers to communities in New Zealand developing age‐friendly initiatives. Methods: A qualitative participatory approach underpinned this study. Semi‐structured digitally recorded individual interviews were undertaken with 24 government officials, local government steering group members and community representatives from an urban city, provincial city and a rural district. A general inductive data analytic process was undertaken. The consolidated criteria for reporting qualitative research (COREQ) guidelines were followed to ensure rigour in this study. Results: (a) Being at the beginning, (b) Minimal diversity and (c) Problems getting started were three key issues identified. Conclusions: New Zealand is in the early stages of becoming age‐friendly. Findings from this study provide a place‐based New Zealand perspective and have influenced central government social policy and practice development, culminating in resources supporting local government and communities to successfully implement age‐friendly initiatives.